PENDIDIKAN ISLAM DALAM PERSPEKTIF EPISTEMOLOGI BURHANIY - Muhamad Asvin Abdur Rohman (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2016)
Soebardi in The Place of Islam states that: (a) institutions boarding schools are the institutions most decisive Islamic character of Islamic kingdoms and the most important role for the spread of Islam to the outposts; (B) of the institutions of boarding that origins a number of manuscripts concerning the teaching of Islam in Southeast Asia, (c) and to be able to truly understand the history of Islamization in the region, we should begin to study these boarding institutions, because tutions is the primary agency arrows spread of Islam in the region. Pesantren education today can be classified into three types. First, the boarding school education and teaching how to use the method sorogan or dam, which is a teaching Kyai of santri based on the classic books written in Arabic, by scholars' medieval translation system. Generall, boarding school is